Persepsi Khalayak Tentang Program “Tau Gak Sih” di TRANS7 - Fajar Irsyad Faturachman; Happy Prasetyawati (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2025)
The "Tau Gak Sih" program is an educational information program included in the megazine tv show which is packaged attractively by doing voxpop to the public. Tau Gak Sih TRANS7 airs every Monday to Friday at 14.00 - 14.30 WIB. In addition to providing information that is not widely known, the Tau Gak Sih program provides educational shows with a relaxed and funny manner. The theory used is social judgment theory and individual difference theory. The research approach uses a quantitative survey method. The sampling technique used was convenience sampling by taking 100 samples of respondents from the program's audience. This study uses only one variable (univariate), namely the variable perception of the Tau Gak Sih program. The results showed that the perception of the audience of the Tau Gak Sih program was good and there was no significant difference. Based on the crossulation, there were differences in perceptions in the sub-dimensions of the narrative.